A New Multilateralism for the 21st Century - Lagarde, Christine (International Monetary Fund, 2014)
This chapter presents the content of the Richard Dimbleby lecture, which has been delivered by an influential business or a political figure every year since 1972. Christine Lagarde, Managing Director of the IMF, delivered the 2014 lecture at Guildhall in London on February 3. The 44 nations gathering at Bretton Woods have been determined to set a new course based on the principle that peace and prosperity flow from the font of cooperation. Fundamentally, the new multilateralism needs to instil a broader sense of social responsibility on the part of all players in the modern global economy. A renewed commitment to openness and to the mutual benefits of trade and foreign investment is requested. It also requires collective responsibility for managing an international monetary system that has travelled light-years since the old Bretton Woods system. The collective responsibility would translate into all monetary institutions cooperating closely mindful of the potential impact of their policies on others.